2022
DOI: 10.9734/ijpss/2022/v34i232501
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Analysis for Fruit Yield in Bottle Gourd [Lagenaria siceraria (Mol.) Standl]

Abstract: Present investigation was carried out during Zaid season 2019-2020 in (Y1) and Zaid 2020-2021 in (Y2) at the Main Experimental Station (MES), Department of Vegetable Science, Acharya Narendra Deva University of Agriculture & Technology, Narendra Nagar, Kumarganj, Ayodhya (U.P) with 21 genotypes with six parental line and their fifteen F1 hybrids of bottle gourd by using diallel (excluding reciprocal) mating fashion. Experiment was laid out in RBD include three replication having each experimental unit with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The magnitude of specific combining ability variance was higher than general combining ability variance for all of the traits viz.,days to first male flower appearance, days to first female flower appearance, node number at which first male flower appearance, node number at which first female flower appearance, number of branch per plant, fruit length, fruit girth, average fruit weight , number of fruit per plant, fruit yield per plant, moisture content, total soluble solids, chlorophyll a, chlorophyll b and total chlorophyll which indicated the importance of non-additive gene effects in the inheritance of these traits, which suggesting exploitation of these traits for improvement of yield through heterosis breeding. The above results were in accordance with the findings of Gayakawad [12], Janaranjani et al [6], Khot et al [10] for days to first male flower appearance; Gayakawad [12], Janaranjani et al [6], Shinde et al [7], Khot [13], Hadiya et al [9], Khot et al [10],Patel and Mehta [11] for days to first female flower appearance; Gayakawad [12], Janaranjani et al [6] for node number at which first male flower appearance; Gayakawad [12], Janaranjani et al [6], Shinde et al [7], Khot [13], Hadiya et al [9], Khot et al [10] for node number at which first female flower appearance; Gayakawad [12], Khot [13], Khot et al [10] for number of branch per plant; Patel et al [5], Gayakawad [12], Janaranjani et al [6], Shinde et al [7], Khot [13], Khot et al [10], Patel and Mehta [11] for fruit length; Gayakawad [12], Janaranjani et al [6], Hadiya et al [9], Patel and Mehta [11] for fruit girth;, Janaranjani et al [6], Shinde et al…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of specific combining ability variance was higher than general combining ability variance for all of the traits viz.,days to first male flower appearance, days to first female flower appearance, node number at which first male flower appearance, node number at which first female flower appearance, number of branch per plant, fruit length, fruit girth, average fruit weight , number of fruit per plant, fruit yield per plant, moisture content, total soluble solids, chlorophyll a, chlorophyll b and total chlorophyll which indicated the importance of non-additive gene effects in the inheritance of these traits, which suggesting exploitation of these traits for improvement of yield through heterosis breeding. The above results were in accordance with the findings of Gayakawad [12], Janaranjani et al [6], Khot et al [10] for days to first male flower appearance; Gayakawad [12], Janaranjani et al [6], Shinde et al [7], Khot [13], Hadiya et al [9], Khot et al [10],Patel and Mehta [11] for days to first female flower appearance; Gayakawad [12], Janaranjani et al [6] for node number at which first male flower appearance; Gayakawad [12], Janaranjani et al [6], Shinde et al [7], Khot [13], Hadiya et al [9], Khot et al [10] for node number at which first female flower appearance; Gayakawad [12], Khot [13], Khot et al [10] for number of branch per plant; Patel et al [5], Gayakawad [12], Janaranjani et al [6], Shinde et al [7], Khot [13], Khot et al [10], Patel and Mehta [11] for fruit length; Gayakawad [12], Janaranjani et al [6], Hadiya et al [9], Patel and Mehta [11] for fruit girth;, Janaranjani et al [6], Shinde et al…”
Section: Resultssupporting
confidence: 90%
“…Which suggested a greater role of non-additive genetic variance in the inheritance of these characters. The predominant role of non-additive gene action was also reported by Patel et al [5], Janaranjani et al [6], Shinde et al [7], Rajkumar et al [8], Hadiya et al [9], Khot et al [10] and Patel and Mehta [11] in bottle gourd.…”
Section: Resultssupporting
confidence: 54%
“…Refs. [40,41] reported high GCA compared to SCA effects for fruit yield, indicating the involvement of additive gene action conditioning their inheritance. Analysis of heterosis in bottle gourd identified the dominant form of heterosis for plant height, fruit length, and the number of branches, aiding the identification of hybrids for use in strategic breeding and variety release [40].…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic correlation coefficient was higher than their corresponding phenotypic correlation coefficient for most of the characters except yield per plant, number of fruits per plant, fruit weight (Table 2). A perusal of data revealed that yield has positive and significant correlation with fruit weight, node at which first female flower appears, node at which first male flower appears had positive correlation coefficient among themselves (Maurya 1994). Higher and positive direct effect (at the genotypic level) on yield was exerted by number of fruits per plants followed by node at which first female flower appears, fruit weight, days to first fruit harvest, number of primary branches, days to first male anthesis and seed length.…”
mentioning
confidence: 97%